From Cholera To Food Poisoning: Exploring The Antidiarrheal Activity Of A Multi-Species Water-Based Probiotic Product - Dodoo, C.C.; Simpson, S.V.; Mensah, G.I.; Fredua-Agyeman, M. (BMC Microbiology, 2025)
Diarrheal diseases are a leading cause of morbidity and mortality worldwide. Given the rising prevalence of antimicrobial resistance among causative diarrheal pathogens, there is an increasing imperative to explore alternative therapeutic strategies. In this study, the potential of Symprove™ (a water-based probiotic product) against diarrheal pathogens, V. cholerae, E. coli, S. aureus, and L. monocytogenes was evaluated. Investigations were carried out using isothermal microcalorimetry and colony counting. The experimental setup consisted of individual cultures and co-incubations of the pathogens and probiotic formulation. Growth curves were obtained for all setups using a thermal activity monitor, and colony counts were performed after 24–48 h for both probiotic organisms and pathogens. The growth curves obtained revealed that co-incubation of E. coli and S. aureus with the probiotic formulation showed a slightly delayed onset of growth for the pathogens although these pathogens were faster growing than the probiotic. For L. monocytogenes, the thermal growth curves showed dominance of the probiotic formulation. Corresponding colony counts revealed significantly reduced bacterial numbers after 48 h when the pathogens were co-incubated with the probiotic formulation. Co-incubating V. cholerae with the probiotic formulation showed a significant reduction in pathogen numbers after 24 h and no counts after 48 h. These findings indicate the possible inhibitory effect of the probiotic formulation and highlight the therapeutic potential of probiotics as alternative approach to conventional antibiotics.
Research Article
Keywords: Cholera; Diarrhea; Gut pathogens; Probiotics